SYNTHESIS AND CHARACTERIZATION OF NEW THERMOSENSITIVE GRAFT COPOLYMERS FROM N-ISOPROPYLACRYLAMIDE AND 2-METHYL-2-OXAZOLINE MACROMONOMERS - Rueda, Juan Carlos (2021)
New graft copolymers were synthesized from the free radical polymerization of N-isopropylacrylamide (NIPAAm) and 2-methyl-2-oxazoline (MM) macromonomers initiated by 2,2'-azobisisobutyronitrile in dimethylformamide. The macromonomers, with polymerization degrees 31 and 62, were synthesized by ring-opening cationic polymerization of 2-methyl-2-oxazoline initiated by chloromethylstyrene in the presence of sodium iodide. The grafted macromonomers and copolymers were characterized by proton nuclear magnetic resonance spectrometry (1H-RMN) and the conformational transition temperature was determined by turbidimetric measurements and 1H-RMN spectroscopy. The NIPAAm / MM molar ratio in the copolymer, determined by 1H-RMN, was higher than in the feed to the reactor due to the higher reactivity of the NIPAAm due to its greater diffusivity in the reacting medium due to its lower molecular weight. The conformational transition temperature (LCST) of the graft copolymers ranged from 33 to 38 °C and the intensity of the same was a function of the molar ratio of NIPAAm / macromonomer within the graft copolymer. The value of the LCST increased, and at the same time its intensity decreased, as the NIPAAm / MM molar ratio decreased in the copolymer. The LCST also decreased even more in intensity as the degree of polymerization of the macromonomer increased. From the LCST temperature, the graft copolymers with a relatively high content of MM could form micelles or molecular aggregates type "core-shell" in aqueous solution, which would be formed by a core with collapsed segments of polyNIPAAm and a shell formed of hydrophilic polymethyloxazoline chains, which partially prevent an intermolecular collapse of these aggregates.